Supporting the Evaluation and Implementation of Musculoskeletal Models of Care: A Globally Informed Framework for Judging Readiness and Success. Issue 4 (April 2017) - Briggs, Andrew M.; Jordan, Joanne E.; Jennings, Matthew; Speerin, Robyn; Bragge, Peter; Chua, Jason; Woolf, Anthony D.; Slater, Helen
Abstract : Objective: To develop a globally informed framework to evaluate readiness for implementation and success after implementation of musculoskeletal models of care (MOCs). Methods: Three phases were undertaken: 1) a qualitative study with 27 Australian subject matter experts (SMEs) to develop a draft framework; 2) an eDelphi study with an international panel of 93 SMEs across 30 nations to evaluate face validity, and refine and establish consensus on the framework components; and 3) translation of the framework into a user‐focused resource and evaluation of its acceptability with the eDelphi panel. Results: A comprehensive evaluation framework was developed for judging the readiness and success of musculoskeletal MOCs. The framework consists of 9 domains, with each domain containing a number of themes underpinned by detailed elements. In the first Delphi round, scores of "partly agree" or "completely agree" with the draft framework ranged 96.7%–100%. In the second round, "essential" scores ranged 58.6%–98.9%, resulting in 14 of 34 themes being classified as essential. SMEs strongly agreed or agreed that the final framework was useful (98.8%), usable (95.1%), credible (100%) and appealing (93.9%). Overall, 96.3% strongly supported or supported the final structure of the framework as it was presented, while 100%, 96.3%, and 100% strongly supported or supported the content within the readiness, initiating implementation, and success streams, respectively. Conclusion: An empirically derived framework to evaluate the readiness and success of musculoskeletal MOCs was strongly supported by an international panel of SMEs. The framework provides an important internationally applicable benchmark for the development, implementation, and evaluation of musculoskeletal MOCs.